Incidence of HCC in chronic hepatitis C patients with advanced hepatic fibrosis who achieved SVR following DAAs: A prospective study. Issue 7 (4th March 2020) - Shiha, Gamal; Mousa, Nasser; Soliman, Reham; NNH Mikhail, Nabiel; Adel Elbasiony, Mohamed; Khattab, Mahmoud
Abstract: Liver cirrhosis is an important risk factor for hepatocellular carcinoma. The reported annual incidence of HCC is about 3%‐8% in CHC cirrhotic patients. Based on the Cochrane systematic review, there was no clear evidence, on the long‐term clinical effects of DAAs in patients achieving SVR, as regard liver cirrhosis‐related HCC incidence. The aim of the study was to determine the incidence of HCC in chronic hepatitis C patients genotype IV with liver cirrhosis and advanced liver fibrosis after achieving SVR following DAA treatment in a prospective large cohort of HCV patients with long follow‐up. This was a prospective observational cohort study including 2372 CHC patients with advanced liver fibrosis or cirrhosis receiving DAA therapy in outpatient clinics at the Egyptian Liver Research Institute and Hospital since January 2015. Liver fibrosis was assessed using transient elastography. Abdominal ultrasonography and AFP measurement were done at baseline and follow‐up visits every 6 months, in addition to triphasic abdominal MSCT when needed. Patients were followed up after achieving SVR12 for at least 12 months. HCC developed in 109 cases during the follow‐up period (mean 23.60 ± 8.25 months). Overall HCC incidence was 2.338/100 PY, 95% CI = 1.942‐2.814. In patients with cirrhosis, the incidence of HCC was 2.917/100 PY, 95% CI = 2.407‐3.535, while in patients with advanced liver fibrosis the incidence of HCC was 0.664/100 PY, 95% CI = 0.333‐1.326. In conclusion, the incidence of HCC was reduced in chronic hepatitis C genotype 4 patients with liver cirrhosis (F4) and advanced hepatic fibrosis (F3) who achieved SVR following DAA therapy.